Extraterritorial Jurisdiction and Head-of-State Immunity: Sovereignty and the Use of Force in the Fragmentation of International Law - Ani Purwati (International Journal of Science and Environment (IJSE), 2026)
The exercise of extraterritorial jurisdiction against a foreign head of state raises fundamental problems in international law because it directly implicates the principles of state sovereignty, head-of-state immunity, and the prohibition of the use of force. Normatively, international law recognizes that an incumbent head of state enjoys personal immunity (immunity ratione personae) from the criminal jurisdiction of other states, grounded in customary international law and international jurisprudence. This principle is reinforced by the Charter of the United Nations, particularly Article 2(4) on the prohibition of the threat or use of force and Article 2(7) on the principle of non-intervention (UN Charter, 1945). However, the practice of some states applies extraterritorial jurisdiction unilaterally under the rationale of global law enforcement or national security, while in practice disregarding head-of-state immunity and the limits of territorial sovereignty. This condition reflects normative fragmentation and the politicization of the application of international law. Regulatory weaknesses are evident in the absence of a comprehensive international instrument governing the limits of extraterritorial jurisdiction over senior state officials, weak enforcement mechanisms for violations of the non-intervention principle, and the lack of effective sanctions outside international judicial fora. This research employs a normative legal method, using approaches grounded in international legal instruments, conceptual analysis, and jurisprudential review, including the Arrest Warrant decision (Democratic Republic of the Congo v. Belgium, 2002). The findings confirm that cross-border law enforcement through coercive measures without the consent of the territorial state or a mandate from the UN Security Council is inconsistent with state sovereignty and the prohibition of the use of force. Therefore, international legal norms should be strengthened through multilateral instruments and lawful accountability mechanisms to safeguard the supremacy of international law.